Body Mass Index status and its relationship with mode of delivery, birth weight and early feeding history among children in an urban area of Pahang - Pasi, Hafizah; Ab Rahman, Jamalludin; Mohd Rus, Razman; Abd. Aziz, Karimah Hanim; Nasreen, Hashima E; Yusof, Muhammad Zubir; Hassan, Noor Artika (Malaysian Medical Association, 2019)
INTRODUCTION: The body mass index (BMI) of children is currently increasing in trends either globally or locally. In Malaysia, the number of children approaching unhealthy BMI is alarming. Despite the frequently conducted studies on children’s BMI and factors such as diet and physical inactivity, limited studies were done focusing on birth related and early life factors. Thus, this research aims to study the body mass index status and its relationship with birth weight, mode of delivery and early feeding history among children in one of the urban residential area in Kuantan, Pahang. METHODS: A cross-sectional study with face-to-face interview using pre-tested structured questionnaires was conducted in October till November 2018. RESULTS: Among 92 participants, majority were male (52.2%), Malay (58.7%), have working parents (70.9%) and within M40 household income category (50.0%). Median age of the participants was 11 years old and mostly had appropriate birth weight, delivered via spontaneous vaginal delivery and weaned after six months with proportion of 87.0%, 77.2% and 75.0% respectively. Children who were wasted and severely wasted constitute 18.5% and overweight and obese 13.1%. Among the three main factors studied, it was found that only age of weaning hassignificant relationship with BMI status among these children (χ2 =7.58 (2), p=0.023). CONCLUSION: Therefore, intervention as early as during infancy, particularly age of weaning, is important in maintaining the healthy BMI status among these children.